In vitro and in vivo antimicrobial activity of cinnamaldehyde and derivatives towards the intestinal bacteria of the weaned piglet. Issue 1 (31st December 2022) - Van Liefferinge, Elout; Forte, Claudio; Degroote, Jeroen; Ovyn, Anneke; Van Noten, Noémie; Mangelinckx, Sven; Michiels, Joris
Abstract: Cinnamaldehyde has an effective antimicrobial activity and therefore it received interest as a feed additive in swine nutrition. However, its high reactivity to amino acid residues might affect its efficacy and digestive processes. As an alternative, 20 chemical derivatives were evaluated. The in vitro antimicrobial activities were tested in an in vitro fermentation model. Thereof three compounds were selected and fed to newly weaned piglets. Five dietary treatments were replicated in six pens of four pigs per pen; i.e. control, cinnamaldehyde at 100 and 400 mg/kg, and 2-methoxycinnamaldehyde and 4-methoxycinnamaldehyde, both equimolar to 400 mg/kg cinnamaldehyde. In vitro results showed that 4-nitrocinnamaldehyde has the highest antimicrobial activity; however, this compound is carcinogenic and was not further issued. Cinnamaldehyde had the second-highest activity, particularly against coliform bacteria and Escherichia coli ( E. coli ), followed by 4-methoxycinnamaldehyde, 2-methoxycinnamaldehyde and hydrocinnamaldehyde. All other derivatives showed lower potency, but they were consistently more bactericidal against coliform bacteria and E. coli as compared to Gram-positive bacteria. At pH 7, aldehydes showed stronger bactericidal activity than their corresponding carboxylic acids, which was not the case at pH 5, suggesting a different mode of action. In the in vivo trial, no significant improvements in animal performance or antimicrobial effects were observed. To conclude, apart from 4-nitrocinnamaldehyde, none of the derivatives showed higher antimicrobial potency than cinnamaldehyde. Three selected compounds from in vitro trials failed to demonstrate major positive outcomes in the in vivo trial. Highlights: 4-Nitrocinnamaldehyde has the highest antimicrobial activity in vitro . Cinnamaldehyde had the second-highest activity, followed by 4-methoxycinnamaldehyde, 2-methoxycinnamaldehyde. No significant improvements in animal performance or antimicrobial effects were observed.